Bilateral Focused Ultrasound Thalamotomy for Essential Tremor (BEST‐FUS Phase 2 Trial). Issue 11 (20th July 2021) - Iorio‐Morin, Christian; Yamamoto, Kazuaki; Sarica, Can; Zemmar, Ajmal; Levesque, Mathieu; Brisebois, Simon; Germann, Jurgen; Loh, Aaron; Boutet, Alexandre; Elias, Gavin J.B.; Azevedo, Paula; Adam, Elizabeth; et al.
ABSTRACT: Background: In patients with medically refractory essential tremor, unilateral magnetic resonance–guided focused ultrasound thalamotomy can improve contralateral tremor. However, this procedure does not address ipsilateral symptoms. Objective: The objective of the current study was to determine whether bilateral thalamotomies can be performed with an acceptable safety profile where benefits outweigh adverse effects. Methods: We conducted a prospective, single‐arm, single‐blinded phase 2 trial of second‐side magnetic resonance–guided focused ultrasound thalamotomy in patients with essential tremor. Patients were followed for 3 months. The primary outcome was the change in quality of life relative to baseline, as well as the answer to the question "Given what you know now, would you treat the second side again?". Secondary outcomes included tremor, gait, speech, and adverse effects. Results: Ten patients were analyzed. The study met both primary outcomes, with the intervention resulting in clinically significant improvement in quality of life at 3 months (mean Quality of Life in Essential Tremor score difference, 19.7; 95%CI, 8.0–31.4; P = 0.004) and all patients reporting that they would elect to receive the second‐side treatment again. Tremor significantly improved in all patients. Seven experienced mild adverse effects, including 2 with transient gait impairment and a fall, 1 with dysarthria and dysphagia, and 1 with mild dysphagia persisting at 3 months. Conclusions: Staged bilateral magnetic resonance–guided focused ultrasound thalamotomy can be performed with a reasonable safety profile similar to that seen with unilateral thalamotomy and improves the tremor and quality of life of patients with essential tremor. Longer‐term follow‐up and continued accrual in the phase 3 trial will be required to validate these findings. © 2021 International Parkinson and Movement Disorder Society